The Accommodation of ASEAN Convention against Trafficking in Persons (ACTIP) in Indonesia Regulation - Jevlin Solim (Universitas Lampung, 2019)
Trafficking in Persons is unarguably one of the largest crime industries in the 21st century that demand a concrete and comprehensive approach to prevent and tackle it. Southeast Asia region is one of the highest regions in terms of supplying, transit, and destination for trafficking in persons victims in the world. ASEAN member states, including Indonesia as key sources of trafficking victims have taken many efforts, one of the latest was ratifying ASEAN Convention Against Trafficking in Persons, Especially Women and Children (ACTIP). And to ensure its effectiveness, the parties need to adjust it with the domestic laws. However, almost 2 years since the ratification, it can hardly be identified any new regulations specifically formed to combat TIPs being enacted to support this convention in Indonesia. Therefore, the objective of this journal is to give insights about the accommodation ACTIP in Indonesia regulation.